Rendering Karakter 3D Virtual secara Real-Time menggunakan Metode Light Estimation pada Augmented Reality Berbasis Lokasi - Kevin Kevin; Liliana Liliana; Kartika Gunadi (Jurnal Infra, 2021)
Augmented reality applications are already widely available on mobile devices, but most augmented reality applications assume that light source always comes from above the object and its direction is always downwards so that the shadow is always right under the object, therefore a method is needed to estimate light so that the direction of shadow produced is more realistic, but can still be run on mobile devices.To answer the problem, light estimation method is used in real-time rendering of AR applications on mobile devices so that the shadow direction from virtual objects rendering is parallel and in the same direction as the shadow direction of real objects in their environment, but still uses resources that can be used on mobile devices.Results in this study indicate that the direction of shadow produced by light estimation method in indoor environment is quite accurate (about 33°) and light enough to be used on mobile devices, because the difference in FPS and RAM usage is almost the same as the usage of application without the use of light estimation method, although there is an increase in CPU and battery usage, it's small enough to still work on a mobile device.